Changing spectrum of renal disease in HIV infection - Jung, O; Haack, H S; Brodt, H-R; Grützmacher, P; Geiger, H; Amann, K; Gröne, H-J; Bickel, M (Deutsche medizinische Wochenschrift (1946), 2013)
Renal disease is a common complication in HIV-infected patients. The causes and spectrum of kidney disease among these patients is extensive, including HIV-related and HIV unrelated causes. Our objective was to assess the changes in distribution of renal disease under antiretroviral therapy (ART). Retrospective analysis of all patients from the Frankfurt HIV Cohort (FHC) who underwent renal biopsy because of chronic, progressive renal disease between 1989 and 2012. Two time periods were defined: 1989-2001 (early period) and 2000-2012 (late period). 69 HIV-infected patients, mostly Caucasian and male, underwent renal biopsy (early period: 22 patients, late period: 47 patients). During the total observation time immuncomplex-mediated glomerulonephritis (26.1 %), hypertensive (20.3 %) and diabetic nephropathy (20.3 %) were the most frequent causes of chronic renal disease. HIV-associated renal diseases were predominant in the first period, whereas hypertensive and diabetic kidney disease accounted for almost 50 % of cases diagnosed in the late period. Other types of renal disease frequently encountered during the late period include renal AA-amyloidosis and tenofovir-related kidney disease. The underlying pathology of renal disease in HIV-infected patients is highly variable and evolving. Since the introduction of HAART, renal disease not directly related to HIV has become the predominant cause, reflecting the growing burden of co-morbidities in this aging population.